Saharan Rock Art: Archaeology of Tassilian Pastoralist Iconography - Holl, Augustin F.C. (Rowman & Littlefield Publishers, 2004)
The Neolithic rock images of Iheren, Algeria are the starting point for Augustin Holl's careful analysis of the iconography of Saharan rock art. Created in the third millennium B.C., the Iheren murals are over 3 meters wide and contain multiple compositions that present an allegorical depiction of the lifeways of Tassilian pastoralists in the Sahara. Holl approaches his task as an archaeologist, examining the various strands of evidence—icons, ideas, motifs, colors, and sizes-and weaving them together into a story that offers a window on the pastoralist worldview through the semiotics of their art. His deconstruction and synthesis of this corpus of material should be of interest to African archaeologists, rock art specialists, art historians, and cultural anthropologists alike.